PENGARUH KEPEMILIKAN MANAJERIAL, UKURAN PERUSAHAAN DAN MANAJEMEN LABA TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) (Studi Kasus Perusahaan manufaktur subsektor Food and Beverage Yang Tercantum Di Bursa Efek Indonesia Tahun 2015-2019) - Teguh Erawati; Lia Indah Sari (Fakultas Ekonomi UNIBBA, 2021)
This study aims to examine how the effect of managerial ownership on CSR disclosure, how company size affects CSR, how the influence of earnings management on CSR disclosure. The study took a sample of manufacturing companies in the food and beverage sub-sector listed on the IDX 2015-2019. The sampling method was nonprobability, and the sampling technique used purposive sampling. The data is obtained in the form of annual report documentation which is regularly published annually by each company. The number of samples obtained were 8 companies listed on the IDX. Company size is measured based on total assets, managerial ownership is measured by total shares owned by management and earnings management is measured by discretionary accruals. The data analysis method used in this study is a classical assumption using a multiple linear regression hypothesis test that is processed using the IBM SPSS 22 software. The results showed that managerial ownership has a significant and positive effect on CSR disclosure. Company size has no influence on CSR disclosure. Earnings management has no influence on CSR disclosure.